Salt and High Blood Pressure the Two Silent Killers: A Nepalese Perspective - Vaidya, Abhinav (Nepalese Heart Journal, 2017)
Hypertension is now a public health problem worldwide. Studies done in the past and in the recent times in Nepal indicate a rising epidemic here as well. Salt is one of the factors always associated with high blood pressure. The article attempts to review this relation, particularly in the context of Nepal. It also touches upon the controversies surrounding salt and blood pressure, and ends with recom-mendations on reducing salt in the diet.